Genetic evidence for introgression between domestic pigs and wild boars (Sus scrofa) in Belgium and Luxembourg: a comparative approach with multiple marker systems. (21st May 2013) - Frantz, Alain C.; Zachos, Frank E.; Kirschning, Julia; Cellina, Sandra; Bertouille, Sabine; Mamuris, Zissis; Koutsogiannouli, Evagelia A.; Burke, Terry
<x xml:space="preserve">Abstract</x> Hybridization between wild species and their domestic relatives can be an important conservation and management problem. Genetic purity of the wild species is desirable per se and the phenomenon can have unpredictable evolutionary consequences. Declining European wild boar populations were frequently restocked with farmed wild boars that sometimes had been crossed with domestic pigs. We used simple polymerase chain reaction‐based diagnostic tests to detect the presence of mitochondrial DNA and coat colour alleles of domestic origin in wild boars from Belgium, Luxembourg, and western Germany. Microsatellite genotypes were used to test for genetic admixture between the wild boars and domestic pigs. Although almost one‐third of all Luxembourg wild boars carried Asian mitochondrial DNA haplotypes originating from domestic pigs, microsatellite‐based clustering only identified four putatively admixed individuals in Luxembourg. By contrast, clustering identified wild boar × domestic hybrids in most sampling locations in Belgium. We interpret these results as evidence of releases of hybrid captive‐reared wild boars. Our results emphasize the need (if working with classical markers) to use different systems to obtain an understanding as to whether hybridization between wild and domestic relatives might have affected the genetic make‐up of a local population. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 110, 104–115.